Preparation and thermal properties of SAT-CMC-DSP/EG composite as phase change material. (5th June 2017) - Mao, Jinfeng; Hou, Pumin; Liu, Rongrong; Chen, Fei; Dong, Xian
Highlights: Improvement of the thermal conductivity by adding thermal conductive fillers as EG. Thermal properties of the composite PCMs containing vary mass ratio of EG. Impact of external heating temperature on the SAT-CMC-DSP/EG with 3 wt% EG. Abstract: In this study, a series of SAT-CMC-DSP/EG (sodium acetate trihydrate-disodium hydrogen phosphate dodecahydrate-carboxyl methyl cellulose/expanded graphite) composite phase change materials (CPCMs) with different mass ratio of EG was prepared. The influence of EG addition on the thermal conductivity was examined using transient plane source method, thermal properties including melting temperature and latent heat were evaluated using differential scanning calorimetry (DSC), the latent heat storage and release time and the degree of supercooling were obtained using cooling curves method. The results showed that as a thermal conductivity enhancer, EG could improve the thermal conductivity of SAT effectively. At the same time, it brings some problems with the increase of EG mass fraction, such as lower enthalpy and higher subcooling degree. The SAT-CMC-DSP/EG with 3 wt% EG was considered as the most suitable choice with the melting temperature, latent heat, thermal conductivity and degree of supercooling were 58.1 °C, 210.7 kJ/kg, 1.37 W/(m K) and 2 °C. The impact of external heating temperature on the composite PCM containing 3 wt% EG was tested. The results showed that the heating temperature is should better not exceed 78 °C. Furthermore, thermal cycling test results indicated that SAT-CMC-DSP/EG showed a good thermal reliability.